The Forbidden Door : Jane Hawk #4 - Koontz, Dean R. 1945- (Dean Ray) (New York : Bantam Books, 2018)
"Jane Hawk--rogue FBI agent and the country's #1 fugitive--confronts her worst nightmare when her enemies strike shockingly close to home in the explosive new thriller from Dean Koontz, bestselling author of The Silent Corner. Jane Hawk thinks her precious five-year-old son is hidden safely away, with vigilant, indomitable friends. But the malice and resources of her powerful adversaries are boundless and their hunters are circling ever closer to the boy, hoping to draw his mother into their trap. Jane's courage, wits, discipline, and skill will be tested as never before, as she searches for a way through an ever-contracting labyrinth of terror"--.
"Jane Hawk--rogue FBI agent and the country's #1 fugitive--confronts her worst nightmare when her enemies strike shockingly close to home in the explosive new thriller from Dean Koontz, bestselling author of The Silent Corner. Jane Hawk thinks her precious five-year-old son is hidden safely away, with vigilant, indomitable friends. But the malice and resources of her powerful adversaries are boundless and their hunters are circling ever closer to the boy, hoping to draw his mother into their trap. Jane's courage, wits, discipline, and skill will be tested as never before, as she searches for a way through an ever-contracting labyrinth of terror"--
Keywords: FICTION / Suspense; FICTION / Action & Adventure; FICTION / Psychological; Suspense fiction; Psychological fiction